Myoepithelioma of parotid gland – a diagnosis of immunohistochemistry - Jyotsna Sahai; Shilpi Sahu; M.B Hoogar; Priyanka Gaikwad (Tropical Journal of Pathology and Microbiology, 2019)
Myoepitheliomas are rare benign tumours occurring from any secretory system of the body having myoepithelial cells. In the salivary glands they have an occurrence of 1% with the parotid gland being the most commonly affected gland. The epithelioid variant consists of nests or cords of round to polygonal cells, with centrally located nuclei and a variable amount of eosinophilic cytoplasm. Since this variant is rare and myoepitheliomas can mimic other benign as well as neoplastic conditions, immunohistochemistry is useful for coming to a conclusive diagnosis. We present a case of epithelioid myoepithelioma diagnosed at our institution with the help of immunohistochemistry.